2011
DOI: 10.5194/hess-15-2179-2011
|View full text |Cite
|
Sign up to set email alerts
|

Water balance modeling of Upper Blue Nile catchments using a top-down approach

Abstract: Abstract. The water balances of twenty catchments in the Upper Blue Nile basin have been analyzed using a top-down modeling approach based on Budyko's hypotheses. The objective of this study is to obtain better understanding of water balance dynamics of upper Blue Nile catchments on annual and monthly time scales and on a spatial scale of meso scale to large scale. The water balance analysis using a Budykotype curve at annual scale reveals that the aridity index does not exert a first order control in most of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 43 publications
(70 reference statements)
2
63
0
Order By: Relevance
“…Tekleab et al (2011) calibrated a simple water balance model against observed streamflow time series and provided the water balances of twenty catchments in the upper Blue Nile basin. The catchment water balance was analyzed using an empirical relationship between the ratio of mean annual actual evaporation to mean annual rainfall and dryness index of the catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Tekleab et al (2011) calibrated a simple water balance model against observed streamflow time series and provided the water balances of twenty catchments in the upper Blue Nile basin. The catchment water balance was analyzed using an empirical relationship between the ratio of mean annual actual evaporation to mean annual rainfall and dryness index of the catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models that allow for a description of the hydrology of the region play an important role in predicting river discharges from ungauged catchments and understanding the rainfall-runoff processes in the catchments in order to enhance hydrological and water resources analysis. As such, a number of models have been developed and applied to study the water balance, soil erosion, climate and environmental changes in the Blue Nile Basin (e.g., Johnson and Curtis, 1994;Conway, 1997;Mishra and Hata, 2006;Kebede et al, 2006;Kim and Kaluarachchi, 2008;Collick et al, 2009;Steenhuis et al, 2009;Tekleab et al, 2011;Tilahun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Zhang et al (2008) and Tekleab et al (2011) used 20 000 simulations for a four-parameter dynamic water balance model, and Uhlenbrook et al (1999) used more than 400 000 model runs for the much more complex HBV model with 12 parameters.…”
Section: Sensitivity Analysismentioning
confidence: 99%